Tyrosine 3-hydroxylase in rat brain and adrenal medulla: hybridization histochemistry and immunohistochemistry combined with retrograde tracing. - Schalling, M (1986)
Rat brain and adrenal gland were analyzed by hybridization histochemistry using an RNA probe complementary to mRNA for tyrosine 3-hydroxylase (TyrOHase; tyrosine 3-monooxygenase, EC 1.14.16.2), by immunohistochemistry using TyrOHase antiserum, and by retrograde tracing using the fluorescent compound Fast blue. Cell bodies in the ventral mesencephalon contained mRNA for TyrOHase, and these cells were also TyrOHase immunoreactive. After injection of Fast blue into the striatum, such double-labeled cells in addition contained the retrograde tracer, showing that these cells send axonal projections to the injection site. These results show that hybridization histochemistry can be used to identify transmitter-specific neuron populations and that their projections can be established.